ACCOUNTING MEASUREMENT AND DISCLOSURE OF LEASE CONTRACTS AND ITS ROLE IN FINANCING PROJECTS AND RATIONALIZING ADMINISTRATIVE DECISIONS (APPLIED STUDY IN UR ENGINEERING INDUSTRIES) - Abdulameer Zamil Lateef (Scholar Express Journals, 2022)
The research aims to identify the role of accounting measurement and disclosure of lease contracts in financing projects and rationalizing administrative decisions, in addition to shedding light on the most important accounting standards that dealt with the subject of leasing, including International Accounting Standard No. (17), with an indication of the role of accounting information in supporting lease decisions. The research was applied in Ur Engineering Industries. The research came to the conclusion that the process of financial evaluation of the lease transaction leads to the transfer of ownership to the lessee at the end of the lease term, and it includes the fixed and irrevocable lease contract, and the accounting measurement and disclosure of lease contracts helps in financing projects and rationalizing administrative decisions.
Keywords: ownership; Industries; decisions; rationalizing